Working for Audiovisual Preservation in Europe - Muller, Anne; de Lusenet, Yola (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
Training is at the heart of the European TAPE project. The project is directed at cultural and research institutions that (also) hold audiovisual materials, as a minority collection in what are usually largely paper-based holdings. TAPE’s training programme includes European workshops (in English) as well as national/regional events (in national languages). Since the start of the project already ten workshops took place, and more will follow.